Marginally Significant Effects as Evidence for Hypotheses: Changing Attitudes Over Four Decades. (July 2016) - Pritschet, Laura; Powell, Derek; Horne, Zachary
Some effects are statistically significant. Other effects do not reach the threshold of statistical significance and are sometimes described as "marginally significant" or as "approaching significance." Although the concept of marginal significance is widely deployed in academic psychology, there has been very little systematic examination of psychologists' attitudes toward these effects. Here, we report an observational study in which we investigated psychologists' attitudes concerning marginal significance by examining their language in over 1, 500 articles published in top-tier cognitive, developmental, and social psychology journals. We observed a large change over the course of four decades in psychologists' tendency to describe a p value as marginally significant, and overall rates of use appear to differ across subfields. We discuss possible explanations for these findings, as well as their implications for psychological research.